2014
DOI: 10.1111/jsap.12186
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial size, atrial function and left ventricular diastolic function in cats with hypertrophic cardiomyopathy

Abstract: Left atrial volume is obtainable by echocardiography in cats. Left atrial volume and atrial function may indicate chronicity and severity of diastolic dysfunction associated with hypertrophic cardiomyopathy and congestive heart failure. Left atrial function was reduced in cats with hypertrophic cardiomyopathy and congestive heart failure compared with healthy and asymptomatic hypertrophic cardiomyopathy groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
75
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(100 citation statements)
references
References 40 publications
18
75
0
7
Order By: Relevance
“…The clinical and prognostic value of LA size (determined echocardiographically) in cats with HCM has been repeatedly demonstrated, and thus is often used as a clinical surrogate of clinical severity and hemodynamic burden 5, 19, 31, 32, 33, 34. In our study, LV free wall thickness, RV chamber size, and RV function (as assessed by 2D TAPSE) were independently correlated with LA size.…”
Section: Discussionsupporting
confidence: 52%
“…The clinical and prognostic value of LA size (determined echocardiographically) in cats with HCM has been repeatedly demonstrated, and thus is often used as a clinical surrogate of clinical severity and hemodynamic burden 5, 19, 31, 32, 33, 34. In our study, LV free wall thickness, RV chamber size, and RV function (as assessed by 2D TAPSE) were independently correlated with LA size.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, detecting cardiac chamber dilatation is crucial for stratifying patients with cardiac disease, and the recommended way to assess LA dilatation in people now is the use of volumetric methods . In cats with cardiac disease, LA volume and LA EF, obtained from volume measurement over the cardiac cycle, have been reported to be useful diagnostic and prognostic echocardiographic variables, showing better performance when compared to simple diameter measurements . One study comparing LA/Ao with LA volume assessment in a population of dogs with MMVD showed that mild LA dilatation could be detected in some dogs only by measuring LA volume, but not LA diameter .…”
Section: Discussionmentioning
confidence: 99%
“…125,136,246,248,254,256,257 Approaches include single and bi-plane length-area or Simpson's methods for estimating volumes and application of different M-mode cursor planes to measure fractional change. These are not widely used but should gain greater favor with adoption of bi-plane 2D and 3D methods.…”
Section: Atrial Functional Indicesmentioning
confidence: 99%
“…125,145,149,150,193,194,198,249,257,[277][278][279][280]315,[427][428][429][430][431][432][433][434][435][436] Most cases are presumed to have a genetic basis, but only a small number of mutations have thus far been elucidated. 125,145,149,150,193,194,198,249,257,[277][278][279][280]315,[427][428][429][430][431][432][433][434][435][436] Most cases are presumed to have a genetic basis, but only a small number of mutations have thus far been elucidated.…”
Section: Etiologies Of Cardiomyopathymentioning
confidence: 99%